Penerapan Sistem Informasi Pendaftaran Anggota Karate Pada Dojo Anak Angin Karate Team Berbasis Website - Dhea Marezkha Alexandra; Feby Farhan Nabila; Eka Rini Yulia (JURNAL TEKNOLOGI INFORMASI, 2026)
Previously, the Anak Angin Dojo Karate Team registered members manually by writing data on paper and sending proof of payment via WhatsApp. During this process, various problems arose, such as data irregularities and long administrative times. The objective of this research is to create a web-based registration information system that helps manage dojo member data more effectively. Requirements analysis, design, implementation, and testing are the steps in the waterfall method sistem development. This sistem is built with the CodeIgniter framework based on PHP and the MySQL database. Member registration, management of coach and athlete data, achievements, training schedules, and submission of biodata changes are the main features developed. The User Acceptance Test (UAT) method is used to assess how well the sistem functions meet user needs. The research results show that the information sistem can replace manual processes with digital processes, speed up the registration process, reduce recording errors, and overall improve the efficiency and accuracy of dojo administrative management.